2017
DOI: 10.1039/c7cp06191a
|View full text |Cite
|
Sign up to set email alerts
|

Towards a dissociative SPC-like water model – probing the impact of intramolecular Coulombic contributions

Abstract: The dissociative water potential introduced by Garofalini et al. proved to be a simple and effective description to account for proton transfer in aqueous media, enabling for instance the execution of simulation studies at different pH values. In this model the charge of each particle is represented by a point-charge surrounded by a Gaussian charge-cloud of opposite sign, thus four Coulombic terms (point-charge-point-charge, point-charge-charge-cloud, charge-cloud-point-charge and charge-cloud-charge-cloud) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Subsequently, all-atomic molecular dynamics simulations (MDS) were performed for the system in BIOVIA Materials Studio 2019 Forcite packages. The simple point charge (SPC) model [35,36], which can accurately describe the water solution environment [37], is adopted for all water molecules.…”
Section: 2mentioning
confidence: 99%
“…Subsequently, all-atomic molecular dynamics simulations (MDS) were performed for the system in BIOVIA Materials Studio 2019 Forcite packages. The simple point charge (SPC) model [35,36], which can accurately describe the water solution environment [37], is adopted for all water molecules.…”
Section: 2mentioning
confidence: 99%
“…The advantage of executing a DFTB-based equilibration over standard force-field approaches is linked to the fact that the formation and cleavage of chemical bonds as required to describe proton-transfer reactions are inherently accounted for in DFTB approaches. Although a number of dissociative/reactive force fields for the treatment of aqueous solutions are available in the literature, , , potential parameters to describe the surface–water interactions have to be provided, which are even more difficult in their construction/balancing compared to nondissociative MM formulations. Because dissociative force fields are typically benchmarked against QM-based simulation results, the outlined QM/MM strategy (at both DFTB and DFT levels) may provide key reference data to verify reactive force fields aimed at the description of proton-transfer reactions near solid-state interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of the parametrization is to ensure compatibility between the novel derived solid-state potentials and the reactive water model. 28,29 The latter explicitly accounts for proton transfer reactions. Therefore, it is not possible to apply various atom types per element.…”
Section: Potential Modelmentioning
confidence: 99%
“…This procedure facilitates effective partial charges rather than relying on integer atomic charges derived from formal oxidation numbers. In addition, the parametrization strategy was based on parameters obtained from a dissociative water model, 28,29 which should enable integration of the novel potential model. A recent study 30 showed that extending a dissociative water model by including solid-state parameters allows MM MD to describe surface phenomena of heterogeneous systems, such as SiO 2 /H 2 O.…”
Section: Introductionmentioning
confidence: 99%